The increased number of osteoblasts and capillaries in orthodontic tooth movement post-administration of Robusta coffee extract - H. Herniyati (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: The application of orthodontic forces subjects blood capillaries to considerable pressure, resulting in hypoxia on the pressure side. Vascular endothelial growth factor (VEGF), expressed in osteoblasts represents an important mitogen that induces angiogenesis. Osteoblasts and blood capillaries play an important role in bone formation. Robusta coffee contains chlorogenic acid and caffeic acid both of which produce antioxidant effects capable of reducing oxidative stress in osteoblasts. Purpose: The aim of this study was to analyze the effects of Robusta coffee extract on the number of osteoblasts and blood capillaries in orthodontic tooth movement. Methods: This research constituted a laboratory-based experimental study involving the use of sixteen male rodents divided into two groups, namely; control group (C) consisting of eight mice given orthodontic mechanical force (OMF) and a treatment group (T) containing eight mice administered OMF and dried Robusta coffee extract at a dose of 20mg/ 100 g BW. The OMF was performed by installing a ligature wire on the maxillary right first molar and both maxillary incisors. In the following stage, the maxillary right first molar was moved to the mesial using Tension Gauze with a Nickel Titanium Orthodontic closed coil spring. Observation was subsequently undertaken on the 15th day by extracting the maxillary right first and second molar with their periodontal tissues. Thereafter, histological examination was performed using hematoxylin-eosin (HE) staining technique to measure the number of osteoblasts and blood capillaries on the mesial and distal periodontal ligaments of the maxillary right first molar. Results: The administration of Robusta coffee extract increases the number of blood capillaries and osteoblasts on both the pressure and tension sides were found to be significantly higher in the T group compared to the C group (p<0,05). Conclusion: Robusta coffee extract increase the number of osteoblasts and blood capillaries, thereby playing a role in improving the alveolar bone remodeling process in orthodontic tooth movement.